Parental Example as an Effort to Harmonize Gender Equality in the Family Based on Titus 2:1-5 - Rivosa Santosa; Jovita Elizabeth Abraham; Amirrudin Zalukhu (PT FORMOSA CENDEKIA GLOBAL, 2023)
God created male and female in His image (Gen. 1:27). According to the image, it means that there is equality of men and women before God. In life, there are indeed differences in performing functions. The man as the husband becomes the head of the household while the wife becomes the helper. This difference aims for harmony and regularity in the order of life in the family. Recently, a feminist movement has fights for equal rights and opportunities between men and women. This movement is closely related to efforts to fight the domination, exploitation, and repression of an unfair system against women. This movement is closely related to efforts to fight the domination, exploitation, and repression of an unfair system against women. The gender equality movement tries to fight for balance, equality, and equivalence of the roles and/or responsibilities of men and women in things that are not natural, such as rights, opportunities, work relations between men and women. In the family, the wife is the co-heir of grace for a husband. The Apostle Peter warned, “Husbands, live wisely with your wives, as the weaker people! Honour them as co-heirs of the grace of life, that your prayers may not be hindered” (1 Peter 3:7). This study uses a descriptive qualitative method using a narrative study approach to Titus 2:1-5.